A prospective study of fully covered self-expandable metal stents for refractory benign pancreatic duct strictures - Bhavik Bharat Shah; Gajanan Ashokrao Rodge; Usha Goenka; Shivaraj Afzalpurkar; Mahesh Kumar Goenka (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims Fully covered self-expanding metal stents (FCSEMSs) are a relatively novel option for treating painful main pancreatic duct refractory strictures in patients with chronic pancreatitis. Herein, we aimed to assess the efficacy, feasibility, and safety of FCSEMSs in this patient group. Methods This prospective single-center study included patients who underwent endoscopic retrograde pancreatography with FCSEMS placement. The primary endpoints were the technical and clinical success rates. A reduction in visual analog scale pain score of >50% compared with that before stent placement was defined as clinical success. Secondary endpoints were resolution of pancreatic strictures on fluoroscopy during endoscopic retrograde pancreatography and the development of stent-related adverse events. Results Thirty-six patients were included in the analysis. The technical success rate was 100% (n=36) and the clinical success rate was 86.1% (n=31). There was a significant increase in stricture diameter from 1.7 mm to 3.5 mm (p<0.001) after stent removal. The mean visual analog scale pain score showed statistically significant improvement. At 19 months of follow-up, 55.6% of the patients were asymptomatic. Stent migration (16.7%), intolerable abdominal pain (8.3%), development of de novo strictures (8.3%), and mild pancreatitis (2.8%) were the most common adverse events. Conclusions FCSEMS placement showed good technical and clinical success rates for achieving pain relief in patients with refractory main pancreatic duct strictures.